Vasoinhibins Prevent Bradykinin-Stimulated Endothelial Cell Proliferation by Inactivating eNOS via Reduction of both Intracellular Ca2+ Levels and eNOS Phosphorylation at Ser1179 - Carmen Clapp; Stéphanie Thebault; Gonzalo Martínez De la Escalera; Fernando López-Casillas; Luis Vaca; David Arredondo Zamarripa; Gabriel Nava; Celina García; Carmen González (MDPI AG, 2011)
Vasoinhibins, a family of antiangiogenic peptides derived from prolactin proteolysis, inhibit the vascular effects of several proangiogenic factors, including bradykinin (BK). Here, we report that vasoinhibins block the BK-induced proliferation of bovine umbilical vein endothelial cells. This effect is mediated by the inactivation of endothelial nitric oxide synthase (eNOS), as the NO donor DETA-NONOate reverted vasoinhibin action. It is an experimentally proven fact that the elevation of intracellular Ca2+ levels ([Ca2+]i) upon BK stimulation activates eNOS, and vasoinhibins blocked the BK-mediated activation of phospholipase C and the formation of inositol 1,4,5-triphosphate leading to a reduced release of Ca2+ from intracellular stores. The [Ca2+]i rise evoked by BK also involves the influx of extracellular Ca2+ via canonical transient receptor potential (TRPC) channels. Vasoinhibins likely interfere with TRPC-mediated Ca2+ entry since La3+, which is an enhancer of TRPC4 and TRPC5 channel activity, prevented vasoinhibins from blocking the stimulation by BK of endothelial cell NO production and proliferation, and vasoinhibins reduced the BK-induced increase of TRPC5 mRNA expression. Finally, vasoinhibins prevented the BK-induced phosphorylation of eNOS at Ser1179, a post-translational modification that facilitates Ca2+-calmodulin activation of eNOS. Together, our data show that vasoinhibins, by lowering NO production through the inhibition of both [Ca2+]i mobilization and eNOS phosphorylation, prevent the BK-induced stimulation of endothelial cell proliferation. Thus, vasoinhibins help to regulate BK effects on angiogenesis and vascular homeostasis.